2017
DOI: 10.7160/aol.2017.090201
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Albanian Agricultural Export: The Gravity Model Approach

Abstract: Despite its huge agricultural potential, Albania has a sharp trade deficit with agricultural commodities. The main focus of this study is to analyse key determinants of its agricultural export. Here we employ baseline gravity model considering conventional gravity variables for Albanian export flows for the period 1996-2013. The Poisson Pseudo-Maximum Likelihood (PPML) regression is used for stepwise estimations of the augmented gravity model, including effects of Albanian Diaspora, exchange rate and price sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 53 publications
7
26
0
1
Order By: Relevance
“…This result suggests that institutional distance between ASEAN countries and their trading partners reduces the ASEAN’s agricultural exports. This study’s findings align with Braha et al (2017) and de Groot et al (2004) who confirmed that exporting countries restrict exports to countries having different institutional frameworks because of adjustment costs, and an additional lack of trust in the security of transactions. As a result, a 1% increase in institutional distance entails a decline in agricultural export of 0.131%.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This result suggests that institutional distance between ASEAN countries and their trading partners reduces the ASEAN’s agricultural exports. This study’s findings align with Braha et al (2017) and de Groot et al (2004) who confirmed that exporting countries restrict exports to countries having different institutional frameworks because of adjustment costs, and an additional lack of trust in the security of transactions. As a result, a 1% increase in institutional distance entails a decline in agricultural export of 0.131%.…”
Section: Resultssupporting
confidence: 86%
“…These findings reflect the fact that higher-income economies tend to engage in product differentiation and specialization; thus, they trade more. This finding is compatible with that of Abbas and Waheed (2015) and Braha et al (2017). In the authors’ estimation, on average, a 1% increase in the GDP of ASEAN and importing countries would increase the ASEAN’s agricultural exports by 0.593% and 0.599%, respectively.…”
Section: Resultssupporting
confidence: 83%
“…The PPML is also found to well-perform in handling zero trade values (Silva and Tenreyr, 2011). The PPML estimation for gravity analysis is applied in many recent studies for its advantages over other similar estimators (Braha et al, 2017;Wood et al, 2017;Ehrich and Mangelsdorf;2018). The empirical exercise of this study is based on the following gravity equation of trade as shown in equation 1.…”
Section: The Empirical Modelmentioning
confidence: 99%
“…It has the potential to achieve income growth and improve the welfare of the nation. Data on agricultural trade export performance were obtained from WDI (Braha et al 2017;Kumar 2010;Barma 2017;Sun and Li 2018;Campi and Duenas 2016;Arribas et al 2009).…”
Section: Agricultural Export Performancementioning
confidence: 99%